Problems and orientations of development - United Nations (CEPAL Review, 1981)
At its nineteenth session, held in Montevideo in May 1981, the CEPAL Secretariat submitted a report entitled “Latin American Development in the 1980s”, for the main purpose of collaborating with the governments of the region in the preparation of a regional programme of action in relation to the new International Development Strategy.